STUDYING THE THEORY OF BOUNDARIES BY ENGINEERING STUDENTS: TYPICAL PROBLEMS AND TIPS FOR OVERCOMING THEM (FROM OWN TEACHING EXPERIENCE) - Репета, Віктор; Репета, Леся (SWorldJournal, 2024)
Becoming a modern engineer is impossible without thorough mathematical training. For technical specialties in institutions of higher education, there is a course of higher mathematics. Boundary theory is an important component of this course. At certain